마녀 이미지가 표현된 현대 패션의 표현유형과 미적 특성 - 권기영; Giyoung Kwon (The Research Journal of the Costume Culture, 2025)
Despite its historical association with oppression, fear, and marginalized femininity, modern reinterpretations of the figure of the witch position it as a symbolic entity combining historical context and literary imagination. This study analyzes contemporary fashion designs that incorporate witch imagery, focusing on the designs' representational methods and aesthetic characteristics. It includes a literature review examining evolving perceptions of witches across different eras as well as visual and formal analyses of post-2010 fashion collections, using image and text materials from Showstudio.com and other online sources. In various realms of visual culture-including art, film and drama, advertising, product design, and halloween costumes-the image of the witch is no longer confined to traditional iconography. Instead, it is continuously reimagined, taking on expanded and multifaceted meanings that attest to its unique and evolving nature. This study identifies two primary expressive types: direct iconographic appropriation, employing traditional motifs such as pointed hats, black cloaks, and pentacles; and metaphorical suggestion, using dark tones, deconstructed silhouettes, and layered styling to imply the witch's essence. The analyses also highlight three aesthetic characteristics: empowered sensuality, expressed through sheer fabrics and dramatic makeup; supernatural mysticism, combining natural and occult symbols; and uncanny playfulness, which subverts traditional motifs through fantasy and humor. Ultimately, the witch in contemporary fashion serves as both a stylistic code and a visual signifier of cultural narrative and identity. This reimagining has contributed to the development of new aesthetic systems in fashion and broadened the visual culture and design innovation discourse.